The occurrence of the filarial nematode Dirofilaria repens in canine hosts from Maio Island, Cape Verde. Issue 1 (1st February 2016) - Marcos, R.; Pereira, C.; Maia, J.P.; Santos, M.; Luzzago, C.; Lauzi, S.; Genchi, C.; Faustino, A.; Puente-Payo, P.
Abstract: The prevalence of canine Dirofilaria infection in Maio Island (Cape Verde) was analysed by serology, morphological and molecular identification of the parasite species. Blood and sera were collected from 150 dogs and 80 cats aged over 6 months from various localities of the island. DNA was extracted from blood and samples were screened by polymerase chain reaction (PCR) using microfilaria-specific primers. No Dirofilaria immitis was found in dogs while D. repens microfilariae were found in 5.3% of dogs and 6% were positive by PCR. The species identity was confirmed by sequencing of PCR products, which showed almost 100% homology with D. repens European sequences published in GenBank. No difference in Dirofilaria infection was observed between males and females or in dogs with different weights. However, older dogs and those from the western part of Maio Island were more frequently infected. No Dirofilaria was found in cats. This study represents the first evidence of D. repens in Cape Verde (West Africa) and highlights the need for implementing control measures and for a better surveillance of dirofilariosis in Africa.